Intersection of Artificial Intelligence and Medical Education (Student Abstract) - Wu, Keefer P.; Tsang, Patricia C. (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
Can advanced AI-driven technologies transform the traditionally arduous educational process in medicine? This study takes a deep dive into how the publicly available OpenAI ChatGPT-3.5 performs in answering board-style questions designed for physicians training to become pathologists. Correctly answering 75% of 543 questions using an engaging and fast-paced format was an impressive performance. It underscores the potential as well as improvement opportunities of using interactive AI in future medical training.